Monitoring of geomagnetic disturbances using the global survey method in real time - Grigoryev V.G. (Solar-Terrestrial Physics, 2019)
A method for forecasting geomagnetic storms using the realization of the global survey method in real time is presented. The method is based on data from the worldwide network of neutron monitors NMDB. Using this method, we analyze the behavior of components of three-dimensional angular distribution of cosmic rays in the interplanetary medium, which were due to the first two spherical harmonics, over the period from 2013 to 2018. We have established that the main parameters that respond to the arrival of geoeffective disturbances of the interplanetary medium at Earth are changes in amplitudes of zonal (north-south) components of cosmic ray distribution. In order to select effective criteria for identifying predictors of geomagnetic disturbances and their possible temporal variations, we have made a retrospective analysis of the relationship between behaviors of the above components and geomagnetic disturbances occurring during the period of interest.